Weather and climate socio-economic impacts in Central America for the management and protection of world heritage sites and the Diquis Delta culture in Costa Rica (a case study) - Amador Astúa, Jorge Alberto (2014)
Artículo científico -- Universidad de Costa Rica, Escuela de Física. 2014